Transition from Diffusion‐Controlled Intercalation into Extrinsically Pseudocapacitive Charge Storage of MoS2 by Nanoscale Heterostructuring. Issue 1 (19th October 2015) - Mahmood, Qasim; Park, Sul Ki; Kwon, Kideok D.; Chang, Sung‐Jin; Hong, Jin‐Yong; Shen, Guozhen; Jung, Young Mee; Park, Tae Jung; Khang, Sung Woon; Kim, Woo Sik; Kong, Jing; Park, Ho Seok
Abstract : 2D nanomaterials have been found to show surface‐dominant phenomena and understanding this behavior is crucial for establishing a relationship between a material's structure and its properties. Here, the transition of molybdenum disulfide (MoS2 ) from a diffusion‐controlled intercalation to an emergent surface redox capacitive behavior is demonstrated. The ultrafast pseudocapacitive behavior of MoS2 becomes more prominent when the layered MoS2 is downscaled into nanometric sheets and hybridized with reduced graphene oxide (RGO). This extrinsic behavior of the 2D hybrid is promoted by the fast Faradaic charge‐transfer kinetics at the interface. The heterostructure of the 2D hybrid, as observed via high‐angle annular dark field–scanning transmission electron microscopy and Raman mapping, with a 1T MoS2 phase at the interface and a 2H phase in the bulk is associated with the synergizing capacitive performance. This 1T phase is stabilized by the interactions with the RGO. These results provide fundamental insights into the surface effects of 2D hetero‐nanosheets on emergent electrochemical properties. Abstract : The extrinsic surface charge‐storage behavior of 2D RGO/MoS2 hybrids translated from diffusion‐controlled intercalation mechanism is demonstrated. The 2D RGO/MoS2 hybrids exhibit a 1T phase of MoS2 at the interface interacting with the RGO sheets, where the Faradaic charge‐transfer process is facilitated by the strong interplay between the redox‐active MoS2 and electrically conductive RGO sheets.